2016
DOI: 10.1900/rds.2016.13.187
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of High-Density Lipoprotein Cholesterol Do Not Predict the Incidence of Type 2 Diabetes in an Iranian High-Risk Population: The Isfahan Diabetes Prevention Study

Abstract: OBJECTIVES:To evaluate the ability of low-level fasting high-density lipoprotein cholesterol (HDLC) to predict the incidence of type 2 diabetes (T2D) in an Iranian high-risk population. METHODS: Seven-year follow-up data (n = 1,775) in non-diabetic first-degree relatives (FDR) of consecutive patients with T2D aged 30-70 years were analyzed. The primary outcome was the diagnosis of T2D based on repeated oral glucose tolerance test (OGTT). We used Cox proportional hazard models to estimate the hazard ratio (HR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In contrast, in the Hawaii-Los Angeles-Hiroshima study, Hirano found that HDL is a predictor of T2DM for Japanese-American and native Japanese people independently of age and gender [ 31 ]. In a population-based longitudinal survey conducted on a cohort of high-risk individuals in Iran, Janghorbani et al showed that low HDL levels are a weak predictor of T2DM independently of age and gender [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the Hawaii-Los Angeles-Hiroshima study, Hirano found that HDL is a predictor of T2DM for Japanese-American and native Japanese people independently of age and gender [ 31 ]. In a population-based longitudinal survey conducted on a cohort of high-risk individuals in Iran, Janghorbani et al showed that low HDL levels are a weak predictor of T2DM independently of age and gender [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lower level of HDL-C, is associated with a higher risk of DM 18 . On the other hand, HDL-C has not been a reliable predictor for DM 28 . Therefore, when ALT increases and HDL-C decreases, the ALT/HDL-C ratio increases and can be a more effective predictor for DM compared to other risk factors 20 .…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, Hirano in the Hawaii-Los Angeles-Hiroshima study found that HDL is a predictor of T2DM, independent of age and gender in both Japanese-American and native Japanese(37). Janghorbani et al in a population based longitudinal survey showed that low HDL level was a weak predictor of T2DM independent of age and gender in a cohort of high-risk individuals in Iran (38).…”
Section: Discussionmentioning
confidence: 97%